Thrift Business Network Analysis at Happy Thrift Stuff - Nana Heriana; Resya Dwi Marselina; Santi Nurul Adha; Alna Azzahra Nur S (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study aims to comprehend and examine the functioning of the thrift business network at Happythrifstuff. The data collection methods utilized in this study encompass interviews and documentation. The research methodology is a descriptive qualitative approach, which entails collecting, organizing, and presenting data obtained during the study to achieve precise and thorough information. The data suggest that the thrift business network at Happythrifstuff acquires items from Bandung (Gede Bage), which are obtained from distributors in Batam (Sumatra), with the leading suppliers in Korea and Japan. The analysis indicates that the thrift company is well-suited for students or individuals who want to establish an enterprise with relatively small cash and the potential for profitable earnings. This is apparent from the original capital expenditure of 40 goods amounting to Rp. 5,740,000, resulting in Rp profit revenue. 1,148,000 from the sale of 40 products. This essay aims to inspire individuals to engage in the second-hand goods industry, to create cash, and to assist in fulfilling everyday necessities.